九龙江流域环境综合治理环保资金使用效益与管理策略研究 = Strategies on fund management for environmental control of Jiulong River - 黄建宏 Huang, Jianhong (2010)
九龙江是福建省的第二大河流，流经龙岩、漳州、厦门 3 个主要设区市的 13 个县（市、区）。九龙江不仅是闽东南沿海地区的主要水源，还是台湾金门地区的战略后备水源，其水资源保护对中国海峡西岸经济区的建设影响重大。鉴于其特殊地位并在中国东南沿海具有典型性，中国环境保护部于 2009 年将九龙江流域环境综合治理列为全国试点。当前，中国各省各流域污染治理普遍面临着资金短缺的突出矛盾，如何开源节流解决资金瓶颈是目前迫切需要破解的难题，也是九龙江流域环境综合治理试点能否顺利开展并获得成就的关键之所在。本研究以九龙江省级环保专项资金管理为切入点，剖析现有资金管理政策与执行效果，运用在南洋理工大学MPA、MME 所学知识，借鉴新加坡先进管理理念，对改进资金管 理政策并最大限度地发挥资金使用效能提出优化策略。研究涉及治理效益指标筛选、单位投资效益分析等方法的运用。本项目的实施无疑对其他省市流域环境综合治理资金的管理具有参考价值。 Jiulong River in Fujian Province is the second largest river, flows through Longyan, Zhangzhou, Xiamen, 3 major municipalities and districts in 13 counties (cities, districts). Jiulong River is not only the main source of water in coastal areas of Southeast Fujian, Taiwan, Kinmen, or strategic reserve water, its water resources protection on construction of the Economic Zone of China a major impact. Given its special status and is typical in the southeast coast of China, the Chinese Ministry of Environmental Protection will Jiulong River in 2009 as a national pilot environment management. At present, China's governance in the provinces 各 watershed pollution shortage of funds faced by the outstanding contradictions, how to cut costs to solve the bottleneck is the urgent need of funds crack problem as well as comprehensive management of Jiulong River environment to carry out the pilot and get smooth the key to success.